Analisis Kemampuan Teknik Dasar Passing Bawah Bola Voli Peserta Ekstrakurikuler di SMPI Amanatul Ummah - Ahmad Fauzen; Taufik Rahman; Winda Nuraisyah (MAN Insan Cendekia Jambi, 2026)
This study aims to identify the level of mastery of basic underhand passing techniques in volleyball among extracurricular participants at SMPI Amanatul Ummah. The method used is a quantitative descriptive approach with a total of 20 students, consisting of 10 male students and 10 female students. The research instrument was an underhand passing skills test that has been modified from the Braddy Volleyball Test. Data collection techniques were carried out through observation and documentation, while data analysis used descriptive percentages to group skill levels. The results showed that of the 10 male students, 30% were in the very good category, 50% were in the good category, and 20% were in the fair category. Meanwhile, of the 10 female students, 70% were in the good category and 30% were in the fair category. In general, the level of underhand passing skills of extracurricular volleyball participants at SMPI Amanatul Ummah was in the good category. This indicates that the students have mastered basic techniques adequately and have the potential to participate in competitions at the school level.